Strengthening asset recovery efforts: A path to mitigating corruption in the public sector - Rita Komalasari; Cecep Mustafa (Integritas: Jurnal Antikorupsi, 2024)
This paper comprehensively analyses the impediments hindering Indonesia's anti-corruption and asset recovery efforts. It advocates for a holistic approach, emphasizing collective action, trust in public office, and the integration of civil forfeiture as essential components of an effective anti-corruption strategy. The ultimate goal is to contribute to a transparent and corruption-free future in Indonesia. We employ a literature-based inquiry method to investigate Indonesia's multifaceted challenges in combating corruption and recovering illicitly acquired assets. Our analysis reveals widespread corruption, weakened institutions, and a lack of trust in public officials hamper Indonesia's anti-corruption and asset recovery efforts. We argue that a holistic approach that combines infrastructural development, social rehabilitation, people em-powerment, and regulatory reforms is essential. Additionally, civil forfeiture, when integrated effectively, can aid asset recovery. To succeed, these efforts must prioritize the restoration of trust in public office. This paper contributes valuable guidance for policymakers and practitioners striving to create a more transparent and corruption-free future in Indonesia, offering a fresh perspective on addressing corruption in an emerging economy.